Pitutur Jawa: Mohon, Mangesthi, Mangesti, Marem Dalam Praktik Konsultan Pajak - Tanti Sasongko Putri; Alfa Rahmiati (Jurnal Proaksi, 2024)
Javanese culture is known for its values that are highly respected, including various life advice, including manners, ethics, justice in law, and social interactions. However, violations of these values are not uncommon. A tax consultant may be in a situation where he or she has to make a decision that raises an ethical dilemma. This research aims to explore how the values in Javanese songs such as Mohon, Mangesthi, Mangastuti, and Marem are reflected in the practice of tax consultants. Using a qualitative method with a concept that links Javanese pitch with tax consultant practice, the data is presented descriptively. The results show that Javanese cultural values have strong relevance to tax consultant practice. They can provide a solid spiritual and moral foundation for tax consultants in carrying out their duties with integrity, commitment to the common good, and awareness of their moral responsibilities as tax advisors. The limitation of this research is that the focus is limited to tax consultant practices based on Javanese cultural values.